Base-mediated regiospecific cascade synthesis of N-(2-pyridyl)pyrroles from N-propargylic β-enaminones. Issue 54 (18th May 2016) - Shen, Jinhai; Yang, Xifa; Wang, Fuyuan; Wang, Yue; Cheng, Guolin; Cui, Xiuling
Abstract : Two birds with one stone: two classical heterocycles, pyrrole and pyridine, were simultaneously installed from one acyclic enaminone precursor for the preparation of N -(2-pyridyl)pyrroles. Abstract : A KOH-promoted regiospecific synthesis of polysubstituted N -(2-pyridyl)pyrroles under transition metal-free conditions has been developed. The pyrrole and pyridine rings were simultaneously installed from acyclic enaminone precursors under mild conditions and generated 1 equiv. of H2 O as the sole byproduct. A series of polysubstituted N -(2-pyridyl)pyrroles were provided in up to 91% yield for 21 examples.